Automated Cyanide Control At Newmont's Lone Tree Mine Using Degussa's Cyplus® CCS Cyanide Control System - Karen Tempel (The Minerals, Metals and Materials Society, 1998)
Newmont's Lone Tree Mine is located 30, miles east of Winnemucca in Humboldt County, Nevada. Starting in February 1994 a pressure oxidation circuit was commissioned to treat refractory gold ores. Gold is leached and recovered from the oxidized slurry in a six-stage carbon-in-leach (CIL) circuit. Lone Tree has been able to maintain tighter control' of cyanide addition and reduce cyanide consumption its CIL circuit through the installation of Degussa's Cyplus® CCS Cyanide Control System in the spring of 2000. 'The Cyplus® CCS, along with additional inputs' from plant sensors, has allowed tor a more efficient and effective control strategy over the manual control method used ,in the past. This paper documents the key aspects of the Cyplus® CCS installation; the development of the control strategy, and the benefits achieved from enhanced control.